Assessing the Mediating Role of Safety Communication Between Safety Culture and Employees Safety Performance - Naji, Gehad Mohammed Ahmed; Isha, Ahmad Shahrul Nizam; Alazzani, Abdulsamad; Saleem, Muhammad Shoaib; Alzoraiki, Mohammed (Frontiers in Public Health, 2022)
The main purpose of this research work was to investigate the mediating role of safety communication (SCO) between safety culture (SC) and safety performance (SP) amongst the employees in the petrochemical industry. Safety communication methods not only enhance working conditions but also have a positive impact on employee’s behaviors and attitudes towards safety and leading towards reduced incidents in the workplace environment. Another goal was to give a holistic model of the connections between safety communication (SC) and employee performance. A stratified sampling with a Likert 5-point scale was used to distribute the questionnaires. Therefore, Hayes’ methods and structural equation modeling (SEM) were utilized to analyze the hypothesized model, then data of about 320 participants were collected from the petrochemical industry. According to our results, four hypotheses have an indirect relationship and significant impact. In addition, the findings reveal that safety communication partially mediates the association between safety culture and safety performance to some extent. The research work-study makes a significant theoretical contribution by focusing on the petrochemical operations of safety culture regarding workplace safety.